A new species of Xylodes Waterhouse from Madagascar, with a key to the genera of the tribe Ptinini from Madagascar, Mascarenes and adjacent regions, and a key to species of Xylodes, subgenus Diegous (Coleoptera: Ptinidae) - Zahradník, Petr; Trýzna, Miloš; Razafindranaivo, Victor (Zootaxa, 2023)
A new species, Xylodes (Diegous) korinae Zahradník & Trýzna sp. nov. (Bostrichoidea: Ptinidae, Ptininae, Ptinini), from east Madagascar is described, illustrated and compared with other species from the subgenus Diegous Pic, 1896. Male and female genitalia are studied and illustrated. Keys to morphologically similar genera from Madagascar and adjacent areas, to both subgenera of the genus Xylodes Waterhouse, 1876, and to all species of the subgenus Diegous are presented. Ecological notes, including photographs of habitats of the new species are also provided.